Analysis of green infrastructure around the homes of nonagenarians in Florianopolis/SC - Buose , Gabriellin; Pfutzenreuter , Andrea Holz (Technical and Scientific Journal Green Cities, 2025)
This study aims to analyze the green infrastructure in an urban area of ​​the city of Florianópolis/SC regarding the quality of life of people aged 90 or over, focusing on the presence of vegetation around the homes of the elderly. The research employed a bibliographic review and photographic survey carried out in February and June 2024. The study fills a gap in the literature by specifically examining the suitability of green infrastructure for nonagenarians, a group often neglected in urban research. The results indicate that, although some areas have adequate sidewalks, the lack of trees along the paths compromises the comfort and safety of the elderly. The presence of green squares is beneficial, but does not replace the need for vegetation on access routes. The study contributes to the understanding of the importance of integrating green infrastructure into urban planning for the elderly population and suggests that urban design should consider green connectivity. Socially, the research highlights the importance of creating more inclusive urban environments for nonagenarians, promoting a better quality of life. Environmentally, it suggests expanding vegetation in urban areas to offer direct benefits to the elderly and the community in general.